Playing and teaching english to adults (2000)
This project tried to answer the query: Can adult students (who have not studied English before) speak English if they are given the opportunities to do it? The high school subjects in question belong to Instituto San Fernando Ferrini. Subjects study at night and they have not studied English before so they were afraid. Results suggested that changing parameters such as speaking in English most of the time and including dynamic activities such as games could help adult students feel better about speaking. Further research is needed to describe how to improve pronunciation and writing in adult students. The project was based on the legal framework of MEN (Ministerio de Educación Nacional: Decreto 3011, 1997) that establishes parameters to teach adult students because they have particular characteristics such as families, children, marriages, responsibilities, etc.